2021
DOI: 10.3390/cells10092191
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Extragastric Diseases—A Focus on the Central Nervous System

Abstract: Helicobacter pylori (H. pylori) is most known to cause a wide spectrum of gastrointestinal impairments; however, an increasing number of studies indicates that H. pylori infection might be involved in numerous extragastric diseases such as neurological, dermatological, hematologic, ocular, cardiovascular, metabolic, hepatobiliary, or even allergic diseases. In this review, we focused on the nervous system and aimed to summarize the findings regarding H. pylori infection and its involvement in the induction/pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 148 publications
(196 reference statements)
0
38
0
1
Order By: Relevance
“…H. pylori infection is associated with several gastric pathologies, such as chronic gastritis, peptic and duodenal ulcers, gastric adenocarcinoma and lymphoma of the mucosa-associated lymphoid tissue [ 4 ]. Epidemiological studies correlate H. pylori infection with various extra gastrointestinal pathologies [ 5 , 6 ], such as ischemic heart disease [ 7 ], glaucoma [ 8 ], cerebrovascular diseases [ 9 ], autoimmune pancreatitis [ 10 ], and neurodegenerative diseases such as Alzheimer’s disease (AD) [ 11 , 12 ], mild cognitive impairment [ 13 ] and Parkinson’s disease [ 14 , 15 ]. Specifically, in the case of AD, the correlation is based on the high incidence of H. pylori in these patients [ 12 , 16 ], as well as by the presence of anti- H. pylori antibodies in their cerebrospinal fluid [ 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori infection is associated with several gastric pathologies, such as chronic gastritis, peptic and duodenal ulcers, gastric adenocarcinoma and lymphoma of the mucosa-associated lymphoid tissue [ 4 ]. Epidemiological studies correlate H. pylori infection with various extra gastrointestinal pathologies [ 5 , 6 ], such as ischemic heart disease [ 7 ], glaucoma [ 8 ], cerebrovascular diseases [ 9 ], autoimmune pancreatitis [ 10 ], and neurodegenerative diseases such as Alzheimer’s disease (AD) [ 11 , 12 ], mild cognitive impairment [ 13 ] and Parkinson’s disease [ 14 , 15 ]. Specifically, in the case of AD, the correlation is based on the high incidence of H. pylori in these patients [ 12 , 16 ], as well as by the presence of anti- H. pylori antibodies in their cerebrospinal fluid [ 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance of intestinal microecology due to H. pylori infection may also be associated with a series of other systemic diseases. Numerous retrospective cohort studies indicated that there was a correlation between positive H. pylori serological test, gut flora disturbance, and the incidence of Alzheimer’s disease ( Baj et al., 2021 ). The gut microbiota creates a natural protective barrier, and secrets numerous neurotransmitters and neuromodulators, such as serotonin, γ-aminobutyric acid, dopamine, or SCFA including acetate, propionate, and butyrate to defend against microorganisms and endotoxin translocation ( Paone and Cani, 2020 ), however, the H. pylori infection could remodel the gut microbiota, which may affect the function of the nervous system by inducing the degeneration and loss of neurons ( Baj et al., 2021 ).…”
Section: Helicobacter Pylori and Gut Microbiomementioning
confidence: 99%
“…Numerous retrospective cohort studies indicated that there was a correlation between positive H. pylori serological test, gut flora disturbance, and the incidence of Alzheimer’s disease ( Baj et al., 2021 ). The gut microbiota creates a natural protective barrier, and secrets numerous neurotransmitters and neuromodulators, such as serotonin, γ-aminobutyric acid, dopamine, or SCFA including acetate, propionate, and butyrate to defend against microorganisms and endotoxin translocation ( Paone and Cani, 2020 ), however, the H. pylori infection could remodel the gut microbiota, which may affect the function of the nervous system by inducing the degeneration and loss of neurons ( Baj et al., 2021 ). Other systematic diseases related to gut microbiota, such as inflammation, dyslipidemia, hyperglycemia, arteriosclerosis, and hypertension could also be affected by H. pylori infection through its impacts on the changes in gut microbiota ( Beydoun et al., 2018 ).…”
Section: Helicobacter Pylori and Gut Microbiomementioning
confidence: 99%
“…Thus, certain researchers sustain that H. pylori eradication was associated with an improvement in levodopa action, clinical symptoms, and life quality in patients with Parkinson’s disease [ 20 ], while others failed to find any association between bacterial eradication and clinical outcomes of Parkinson’s disease [ 110 ]. A recent review pointed out that the host’s innate immunity represented by toll-like receptor 2 might represent the underlying link between this neurological condition and H. pylori infection [ 100 ] ( Table 1 ).…”
Section: H Pylori and Neurological Conditionsmentioning
confidence: 99%
“…Oppositely, Gerges et al found a significantly higher H. pylori seropositivity in Egyptian multiple sclerosis patients, especially those with secondary progressive forms [ 103 ]. Moreover, Baj et al also reported both harmful and protective effects of H. pylori infection on multiple sclerosis [ 100 ] ( Table 1 ).…”
Section: H Pylori and Neurological Conditionsmentioning
confidence: 99%